The makespan problem of scheduling multi groups of jobs on multi processors at different speeds - Ding, Wei (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2012)
In the paper we mainly study the makespan problem of scheduling n groups of jobs on n special-purpose processors and m general-purpose processors at different speeds. We first propose an improved LPT algorithm and investigate several properties of this algorithm. We then obtain an upper bound for the ratio of the approximate solution T to the optimal solution T* under the improved LPT algorithm.